Uma formulação para a integração de um problema clássico de dimensionamento de lotes com o problema do job shop - Renato Luiz de Souza Bastos (2013)
This dissertation is related to the development and implementation of a mathematical model in order to make an integration between lot sizing problem and scheduling problem. The analyses were done according to two policies that are different due to the planning time. The proposal for the first policy is treat the scheduling problem according to Manne and Wagner models in a planning horizon of one week. In the second policy, the inventory cost of work in process is considered, since the data of demand is available, and the objective is to minimize the total cost of a problem scheduled for three weeks. Therefore, the lot sizing problem is the same in both of them. The goal of the integrated model is determine the amount and the sequence of each job, providing need information to production planning of industries. The job shop is the scheduling problem considered, in wich each job has a specific production sequence, named technological factory sequence, with each production operation in a machine known. The decision about the amount of products to be produced and its schedule is the context of Operational Planning sector in manufacturing industry.